2011
DOI: 10.1002/jmri.22497
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of vertebral bone marrow perfusion using dynamic contrast‐enhanced MRI: Initial results in osteoporotic patients with acute vertebral fracture

Abstract: Purpose: To evaluate the potential of quantitative dynamic contrast-enhanced MRI (DCE-MRI) in vertebral bone marrow (vBM) of patients with acute osteoporotic vertebral compression fractures. Materials and Methods:Twenty-six patients with acute osteoporotic fractures (16 female, 10 male, median age 72, range 48-89) and 10 subjects without known history of osteoporosis (6 female, 4 male, median 65, range 31-77) were examined 2D-DCE-MRI. Region of interest (ROI) data in fractured (n ¼ 26) and normal-appearing ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
0
15
0
1
Order By: Relevance
“…Quantitative analysis requires the additional measurement of an arterial input function and a tracer kinetic analysis to derive perfusion and permeability parameters. Previous works have primarily employed semiquantitative analysis on bone marrow DCE data and there are only a few studies using quantitative analysis tools and especially addressing the effect of the presence of the fat signal on the extracted perfusion metrics …”
Section: Technical Aspects Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…Quantitative analysis requires the additional measurement of an arterial input function and a tracer kinetic analysis to derive perfusion and permeability parameters. Previous works have primarily employed semiquantitative analysis on bone marrow DCE data and there are only a few studies using quantitative analysis tools and especially addressing the effect of the presence of the fat signal on the extracted perfusion metrics …”
Section: Technical Aspects Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 99%
“…Furthermore, maximum enhancement [E(max)] and enhancement slope [E(slope)] are significantly decreased in osteoporosis in at least the femurs and vertebrae (114)(115)(116)(117)(118). Quantitative parameters of blood flow were studied with DCE-MRI in osteoporotic patients with acute vertebral fracture compared to a control group (119). Plasma flow (mL/100 mL/min) quantifies the volume of plasma flowing through the region of interest per unit time; plasma volume (mL/100 mL) corresponds to the volume of the plasma per tissue volume in the region of interest and extraction flow (mL/100 mL/min) characterizes the net flow between the plasma and the interstitial space (extracellular and extravascular space).…”
Section: Mrimentioning
confidence: 99%
“…Although use of population-derived arterial input function showed improved reproducibility in at least one study of 23 cancer patients [26], an automated technique was shown to be superior to both population-based arterial input function and placement of ROI on a major artery [27,28]. The presence or absence of osteoporosis or osteopenia within subjects was not specifically addressed and has been shown to have a significant effect on quantitative perfusion parameters [29]. This is a confounding factor with respect to age and may skew results toward a generalized decrease in kinetic parameter values with age secondary to a common pathologic process.…”
Section: Bmentioning
confidence: 99%